Niveles de gallinaza y su efecto en Vigna Sesquipedalis (L) Fruwirth (chiclayo verdura) como forraje en Zungarococha Iquitos 2022 - Medina Medina, Dante Ismael (2024)
The rehearsal was executed in Iquitos, in the Project Agrostologico, organic payment of estiercol of posture birds was used in several dose by square meter, with the purpose of seeing the effect in the production forager of the Chiclayo greenness, the community was formed by 480 plants of the species in study, and the sample they conformed it 4 plants for each treatment, the DBCA was used with 4 treatments and 3 repetitions, the treatments were (T0 = 0 gallinaza kg/m2, T1 = 30 kg/m2, T2 = 40 kg/m2 and T3 = 50 kg / m2 of the payment organic gallinaza). Being reached the conclusion that, if effect significance exists in the yield of the forager of the studied species and that the best averages present it the T3 with respect to the Height (93.17 cm); green Matter (5.10 kg/m2) and dry Matter (1,10 kg/m2) respectively, reason why it is determined that the forage of Chiclayo greenness is an alternative for the animal feeding in our region of amazon low forest due to the nutritional kindness that it presents, for what the hypothesis formulated work presently is accepted.